PROTECTION OF SUSTAINABLE FOOD AGRICULTURAL LAND AGAINST THE CONVERSION OF AGRICULTURAL LAND TO NON-AGRICULTURAL (STUDY IN BANGKALAN) - Astiti, Yunita Fenditia; Yogahastama, Riesta (Faculty of Law Universitas Trunojoyo Madura, 2022)
Protection of Sustainable Food Agricultural Land which is then stated in Regional Regulation No. 05 of 2013 is one of the policies of the Bangkalan Regional Government to reduce the rate of conversion of agricultural land to non-agricultural. The policy is indicated to be ineffective in its implementation in the community because the substance, structure, and culture of the community do not support the existence of the policy. This type of research is empirical research or commonly called field research that can uncover facts in the field. The type of research used is sociological juridical that can observe the reactions and interactions that occur when a norm does not work properly. The approach method used is the fact approach and the legislation approach. Data types and sources use primary data and secondary data, data collection methods use interviews with several communities and related agencies. Then it is analyzed using a descriptive-qualitative method. The results of the research in the application of the Bangkalan Regional Regulation will be tested for its effectiveness in the community when viewed from the civil law aspect which tends to be very lacking to be applied which has an impact on there are still communities transferring their land for personal interests due to the lack of incentives provided by local governments.